ChemInform Abstract: A Practical and Mild Chlorination of Fused Heterocyclic N‐Oxides. Issue 19 (May 2015) - Wang, Dong; Jia, Hailing; Wang, Wuchang; Wang, Zhe
Abstract: The Vilsmeier reagent is employed as both activating agent and nucleophilic chloride source for the regioselective chlorination of quinoline‐ and isoquinoline‐N‐oxides.